PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM MEWUJUDKAN MERDEKA BELAJAR DI MI LIRBOYO - Kurniawan, Wakib; Nawawi, Muhammad Latif; Andrianto, Dedi; Rohmaniah, Siti (STIT AL MULTAZAM, 2023)
This study aims to describe Contextual Teaching and Learning (CTL) learning in realizing independent learning in MI / SD. The method in this research is literature study. Literature study research is usually referred to as bibliography. Literature study can be done by reviewing or searching in various scientific papers, research reports relevant to the problem being studied, books as reinforcing references, scientific magazines, newspapers and so on. To understand a concept in learning is one of the learning objectives itself and understanding this concept has been determined by the government. Learning concepts will be easier to understand if students are able to interpret the concept well. The results of this study indicate that through Contextual Teaching and Learning (CTL) learning, students are able to understand a learning concept by linking it to everyday life, so that students can capture the concept as a whole. Contextual Teaching and Learning (CTL) learning itself has important components that are not owned by other learning. The main components of Contextual Teaching and Learning (CTL) are; Contructivism, Questioning, Inquiry, Learning Community, Modeling, Reflection and Authentic Assessment. With these components that will help students in understanding and interpreting a concept / learning material as a whole and well by linking it to everyday life.